Deep-tissue localization of magnetic field hyperthermia using pulse sequencing. (1st January 2021) - Tansi, Felista L.; Maduabuchi, Wisdom O.; Hirsch, Melanie; Southern, Paul; Hattersley, Simon; Quaas, Rainer; Teichgräber, Ulf; Pankhurst, Quentin A.; Hilger, Ingrid
Abstract: Objective: Deep-tissue localization of thermal doses is a long-standing challenge in magnetic field hyperthermia (MFH), and remains a limitation of the clinical application of MFH to date. Here, we show that pulse sequencing of MFH leads to a more persistent inhibition of tumor growth and less systemic impact than continuous MFH, even when delivering the same thermal dose. Methods: We used an in vivo orthotopic murine model of pancreatic PANC-1 cancer, which was designed with a view to the forthcoming 'NoCanTher' clinical study, and featured MFH alongside systemic chemotherapy (SyC: gemcitabine and nab-paclitaxel). In parallel, in silico thermal modelling was implemented. Results: Tumor volumes 27 days after the start of MFH/SyC treatment were 53% (of the initial volume) in the pulse MFH group, compared to 136% in the continuous MFH group, and 337% in the non-treated controls. Systemically, pulse MFH led to ca. 50% less core-temperature increase in the mice for a given injected dose of magnetic heating agent, and inflicted lower levels of the stress marker, as seen in the blood-borne neutrophil-to-lymphocyte ratio (1.7, compared to 3.2 for continuous MFH + SyC, and 1.2 for controls). Conclusion: Our data provided insights into the influence of pulse sequencing on the observed biological outcomes, and validated the nature of the improved thermal dose localization, alongside significant lowering of the overall energy expenditure entailed in the treatment.